Rapid weight reduction does not impair athletic performance of Taekwondo athletes - A pilot study - Yang, W.-H.; Heine, O.; Grau, M. (PLOS ONE, 2018)
In combat sports such as taekwondo (TKD), athletes rapidly reduce body weight to achieve a desired weight category. Competition takes place 16-24 h after weigh-in and thus, the recovery time is an important factor for competition performance. The purpose of this study was to investigate the impact of rapid weight reduction (RWR) on athletic performance and associated hemorheological properties considering relevant recovery time. Five male TKD athletes reduced body weight by 5% within 3½ days. A simulated competition day (SCD) was carried out after a 16 h recovery period. Parameters were measured before RWR, at weigh-in and before and after three TKD simulation matches (SMs) at SCD. Same set-up was conducted but without RWR as control. Basal blood parameters, red blood cells (RBC) deformability and aggregation, serum glucose and fibrinogen were determined. During SMs, heart rate (HRpeak, HRmean), oxygen uptake (VO2peak, VO2mean), peak lactate (Peak La-), difference of lactate (DeltaLa) and energy systems (anaerobic-alactic, -lactic and aerobic) were analyzed. Basal blood parameters remained unaltered during the interventions. RBC deformability was reduced and aggregation was increased after RWR but values returned to baseline after recovery and were not affected by the SMs. Glucose level was not affected by the interventions. Kick frequency in SMs was higher after RWR which might be responsible for higher HRpeak, VO2peak, VO2mean, Peak La-, DeltaLa- and aerobic demand. The 16 h recovery is sufficient to regenerate measured physiological and hemorheological parameters. TKD-specific performance was not negatively affected during SMs after RWR.